2008
DOI: 10.1007/s10765-008-0525-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Dynamic Plane Source Method

Abstract: Three sources of errors in the extended dynamic plane source (EDPS) method caused by the discrepancy between experiment and model are analyzed. The source effect is eliminated by introducing the nuisance parameter R 0 and the surface effect by a surrounding vacuum. The original model assumes a constant heating power but a constant current is used in the experiment. Suppression of this effect leads to a new solution of the heat equation designated as the constant-current model. The measurements on polymethylmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The thermal parameters were measured using thermal analyser Isomet 2104 (Applied Precision Ltd., Slovakia) and a surface probe with a measuring range of 0.04-0.3 W m -1 K -1 . The measurement procedure is based on the DPS method described by Malinarič and Dieška (2009). A mathematical description was presented in detail by Wakeham et al (1991) and Liang (1995).…”
Section: Methodsmentioning
confidence: 99%
“…The thermal parameters were measured using thermal analyser Isomet 2104 (Applied Precision Ltd., Slovakia) and a surface probe with a measuring range of 0.04-0.3 W m -1 K -1 . The measurement procedure is based on the DPS method described by Malinarič and Dieška (2009). A mathematical description was presented in detail by Wakeham et al (1991) and Liang (1995).…”
Section: Methodsmentioning
confidence: 99%
“…In situations of the best fit, both parameters λ and a can be determined. The method of fitting based on least-squares procedure was described in detail (Malinarič, 2004). Rheological data are important in product quality evaluation, engineering calculations and process design.…”
Section: Methodsmentioning
confidence: 99%
“…The method can be used for thermophysical parameter measurements of polymeric materials, but heat losses from lateral sides of the sample are still problematic. Although the influence of heat losses was estimated in [6] to be much below 1 %, the measurements on polymethylmethacrylate (PMMA) in vacuum showed that it is about 4 % [8]. It could be expected taking into account that the thermal conductivity of air is about 0.025 W·m −1 ·K −1 compared to that of PMMA which is 0.2 W·m −1 ·K −1 [9].…”
mentioning
confidence: 99%